« À la garde de Dieu et à la conduite du voiturier. » Recours et litiges face aux aléas du transport de marchandises (Lyon, milieu xviie s.-xviiie s.) - Benoît Saint-Cast (Clio@Themis)
In early modern France, land and water transport had no insurance system nor legal codification as existed in maritime law. Based on the case of Lyons in the 17th and 18th centuries, the aim of this study is to understand how merchants could prevent transportation risks and claim remedies in case of damage or loss of their goods. The article shows how urban authorities and commercial jurisdictions participate to regulate the transport market and to settle the disputes between merchants and transport intermediaries, setting base to a codification of transport law in the beginning of the 19th century.